PENGARUH MEDIA FILM LASKAR PELANGI TERHADAP KETERAMPILAN MENULIS PUISI AKROSTIK SISWA KELAS V SD - Bagas Satria Badalu; Rosidah, Cholifah Tur (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The problems behind this research are students' skills in writing acrostic poetry, lack of use of learning media, lack of teacher attention to students in practicing writing acrostic poetry. The aim of this research was to determine the influence of the Laskar Pelangi film media on the acrostic poetry writing skills of fifth grade elementary school students. This type of research uses quantitative research with a "quasi experimental design" research design with posttest only control. The population in this study was class V students at SDN Kepuh Kuncian I Waru Sidoarjo, totaling 110 students, and the sample used was class V-B, totaling 29 students and V-C, totaling 26 students. The sampling technique is Random Sampling. Data collection techniques use tests and student response questionnaires. Results of the average test scores for the experimental class and control class. The experimental class had the highest score of 100 and the lowest was 38, while the control class had the highest score of 83 and the lowest of 23. This was proven by the results of hypothesis testing using the Independent Sample T-test which showed a sig. (2-tailed) with a value of 0.000, the results show that the Laskar Pelangi film media has a great influence on the acrostic poetry writing skills of fifth grade elementary school students.